The impact of urban air pollution on human health - N. Komilova; K. Egamkulov; M. Hamroyev; K. Khalilova; D. Zaynutdinova (Medičnì Perspektivi, 2023)
Atmospheric air can be polluted as a result of the ingress of various chemicals into it, which have a harmful effect on human health, causing an exacerbation of cardiovascular, airborne diseases, diseases of the gastrointestinal tract and the endocrine system, and exceeding the norms of dust content in the air leads to an increase in incidence of allergies and bronchial asthma. The relevance of the subject under study lies in the investigation of the sources of air pollution, as they lead to an increase in the degree of morbidity and mortality among the population. This, in turn, requires a radical change in the way people live, as well as the adoption of specific measures to ensure the reduction of air pollution. In this regard, the objective of this study was to perform a comprehensive analysis of the ecological and hygienic conditions of atmospheric air and evaluate its impact on human health due to pollution. The study incorporated empirical research methods such as empirical description and comparison to analyze emissions of pollutants, assess population morbidity rates, and conduct correlation and regression analyses. Official data from the State Committee of Uzbekistan on Statistics and scientific papers were utilized, alongside statistical analysis techniques and logical reasoning to investigate atmospheric air pollution and its impact on public health. The study analysed the indicators of emissions of pollutants into the atmosphere in the Republic of Uzbekistan as a whole and by regions. Furthermore, the paper provides a detailed analysis of the general morbidity of the population of the Republic of Uzbekistan and indicators of the incidence of cardiovascular diseases, based on which a correlation and regression analysis was performed. In addition, the morbidity rates of the population with diseases of the respiratory system and eye diseases throughout the Sirdaryo Region were analysed.  The study revealed that Uzbekistan experiences high levels of environmental pollution, with a direct correlation found between atmospheric pollutants and the incidence of cardiovascular diseases, respiratory organ issues, and eye conditions. To protect the atmosphere, reducing pollutant emissions and implementing sustainable development principles, such as industrial modernization and the use of alternative energy sources, are necessary. The results highlight the importance of identifying pollutant types, their properties, and release conditions for effective pollution assessment. The practical significance of this study is to optimize the data of environmental monitoring of urban air pollution in the Republic of Uzbekistan, where in general there is a high level of pollutants in the atmosphere, which affects the health of the population.